(untitled) (Medicine Today, 2026)
Introduction with Objective: Self-evaluation of faculties is a process in which instructors reflect on their teaching, research, and service activities and assess their own performance in these areas. According to curriculum 2012 phase IV include Medicine and Allied subjects, Surgery and Allied subjects, Gynecology and Obstetrics. The aim of the present study was to find the self assesment of Phase IV faculty at government medical colleges in Mymensingh division. Methods: This cross-sectional descriptive type of observational study was carried out among 166 participants within the defined period from January 2023 to December 2023. The study was carried out among faculties of phase IV of three government Medical Colleges of Mymensingh division. The sampling method of this study was purposive type non-probability sampling. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science named SPSS 25.0 Result: The mean age of the respondents was 48.37±5.33 years. Majority of the respondents were male (136, 82%) and rest were female (30, 18%). Only 64.5% of respondents were completely informed about curriculum outline and assessment process of disciplines just after joining. Majority of the respondents were almost satisfied (59.0%) about their own teaching capabilities. However, whom were not completely satisfied, 41% needed research method, 36.1% needed information technology, 30.1% needed teaching method, 25.9% needed instruction material design, and 24.7% needed assessment method to develop the teaching capabilities. To support for faculty development, 51.8% respondents had attended any training programs. 100% respondents had knowledge about internet use. 99.4% knew power point, 95.2% knew Microsoft word, 30.3% had Excel and 19.4% had SPSS knowledge. Conclusion: In conclusion, the study on faculties of Phase IV in government medical colleges of the Mymensingh division offered a comprehensive overview of various aspects related to demographics, knowledge, self-satisfaction, faculty development initiatives and computer literacy. Medicine Today 2026, Vol.38 (1): 99-102